Faktor penentu keberhasilan risiko dalam operasional bisnis - Fauzi, Moh. (Maliki Interdisciplinary Journal, 2025)
Risk management is a crucial element in ensuring the sustainability and effectiveness of business operations amidst the dynamics of an uncertain business environment, including regulatory changes, economic fluctuations, and environmental risks. The main problem in this study is the low effectiveness of risk management implementation in various business sectors, which has an impact on operational vulnerability and potential financial losses. This study aims to identify factors that determine the success of implementing risk management in company operations. The approach used is a literature review of various secondary sources such as scientific journals, books, and recent research reports. The results of the study indicate that the success of risk management is determined by internal factors such as Return on Assets (ROA), company size, effectiveness of internal control, whistleblowing system, and positive risk culture. Meanwhile, external factors such as macroeconomic conditions, changes in government policy, and environmental risks also contribute significantly. The proposed solution is the integration of risk management into all business processes through visionary leadership, data-based decision-making systems, and strengthening a risk-aware organizational culture. In conclusion, the success of risk management depends not only on technical procedures, but also on the organization's holistic readiness to face uncertainty. The results of this study are expected to be a strategic reference for business actors in building a risk management system that is adaptive, sustainable, and responsive to today's business challenges.